THE CRITICAL ROLE OF UNIVERSITIES IN IMPACTING UPON ENGLISH EDUCATION IN JAPAN - Hasegawa, Hiroshi (PEOPLE: International Journal of Social Sciences, 2017)
Learning a foreign education is compulsory in the Japanese primary and secondary school curricula, with most schools selecting English as their foreign language. Japan’s MEXT (Ministry of Education, Culture, Sports, Science and Technology) clearly identifies one of the main aims in teaching foreign languages is to improve students’ ability to communicate in the target language. However, many students in Japan continue to think of themselves as having only limited oral English communication skills, and are not confident when interacting orally. The majority of Japanese students are primarily externally-motivated English learners: they study simply to pass examinations. Thus students’ motivation for studying English isinconsistent with the Ministry’s aim in teaching it. Despite this, the current lack of opportunity for students to practise their English communication skills could be overcome by implementing systematic plans and achievable strategies. To enable the provision of such opportunities, the role of Japan’s higher education institutions, including universities, must be reassessed. This paper sets out ways in which universities can play a critical role in promoting practical strategies for improving and positively influencing students’ practical English skills in primary and secondary schools. The paper discusses three key suggestions for improving the use of English as an oral communication tool: (1) the inclusion of oral performance in English in the university entrance examination, (2) the development of coherent learning processes for achieving specified outcomes at the university level, and (3) the introduction of teacher-training opportunities for current university lecturers of English.